Performance of Sudanese Desert Lambs Fed Graded Levels of Roselle (Hibiscus sabdariffa) Seeds Instead of Groundnut Cake - Beshir, Amani A.; Babiker, Salih Ahmed (Pakistan Journal of Nutrition, 2009)
The present study was conducted to evaluate roselle (Hibiscus sabdariffa) seed cake as a possible protein supplement for growing Iamb in comparison to groundnut cake. Graded proportion of roselle seed (RS) (0, 10, 20%) which replace Groundnut Cake (GNC) were incorporated in three diets iso-caloric, iso-nitrogenous diets for lambs. Diet A contained 0% Roselle seed while diets B and C obtained 10 and 20% roselle seed respectively. Thirty yearling male lambs of Sudan desert sheep ecotype Kabashi with average body weight of 25.2 kg were used for feeding trial. There was a significant (p